Production of Bacteriocins in a Liquid Medium by Streptococcus mutans - Delisle, Allan L. (1975)
A sterile-filtered, liquid medium composed of one-half-strength APT broth and 4% (wt/vol) yeast extract was found to support the production of bacteriocins by Streptococcus mutans strains BHT and GS-5. Culture supernatants, adjusted to pH 7.0 and sterilized by filtration, contained bacteriocin-like activity, which could be demonstrated by spotting dilutions onto top agar lawns seeded with Streptococcus pyogenes as the sensitive indicator and by adding dilutions to log-phase indicator broth cultures. A quantitative assay was developed for BHT bacteriocin, based on its lethal effects. Bacteriocin production did not occur until after the log phase of growth had ceased and was not inducible by ultraviolet irradiation or treatment with mitomycin C. Non-bacteriocinogenic clones of strain BHT occurred spontaneously at high frequency, suggesting control by a plasmid, but this frequency was not increased by treatment with the plasmid-curing agents acridine orange and ethidium bromide.